2023
DOI: 10.1029/2022jf006817
|View full text |Cite
|
Sign up to set email alerts
|

Transient Freeze‐Thaw Deformation Responses to the 2018 and 2019 Fires Near Batagaika Megaslump, Northeast Siberia

Abstract: Wildfires in Arctic regions impact landforms via permafrost degradation and subsequent deformation that can last for many years. However, it remains uncertain on if and how much deformations occur, and what controls their magnitude, particularly during the first couple of years. Here, we examine the transient post‐fire deformation responses near the Batagaika megaslump, which is the world's largest retrogressive thaw slump at Batagay, Sakha Republic. There were wildfires in the summers of 2018 and 2019 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Anders et al, (2020) performed three TLS measurements over 14 months (June 2015, Aug 2015 and Aug 2016) to observe thaw subsidence of a permafrost area in Northwest Territories, Canada, finding a total change of 1.4 cm; they determined that the TLS measurements were more accurate than those from field-based surveying. Another approach to quantify the effect of seasonal freeze/thaw dynamics on topography is through the use of InSAR remote sensing (de la Barreda-Bautista et al, 2022;Kou et al, 2021;Yanagiya et al, 2023) which can be an effective method to detect the signal of subsidence. Due to its coarser spatial resolution, however, it is likely to underestimate actual heave and subsidence values of smaller isolated features such as palsas.…”
Section: Intra-annual Terrain Dynamics On Palsasmentioning
confidence: 99%
“…Anders et al, (2020) performed three TLS measurements over 14 months (June 2015, Aug 2015 and Aug 2016) to observe thaw subsidence of a permafrost area in Northwest Territories, Canada, finding a total change of 1.4 cm; they determined that the TLS measurements were more accurate than those from field-based surveying. Another approach to quantify the effect of seasonal freeze/thaw dynamics on topography is through the use of InSAR remote sensing (de la Barreda-Bautista et al, 2022;Kou et al, 2021;Yanagiya et al, 2023) which can be an effective method to detect the signal of subsidence. Due to its coarser spatial resolution, however, it is likely to underestimate actual heave and subsidence values of smaller isolated features such as palsas.…”
Section: Intra-annual Terrain Dynamics On Palsasmentioning
confidence: 99%
“…Yanagiya and Furuya (2020) demonstrated the deformation of permafrost surfaces after a 2014 fire in Siberia, where more than 3 million m 3 of permafrost thawed, leading to irreversible subsidence. Yanagiya et al (2023) built on those findings by studying additional geomorphic impacts of 2018 and 2019 fires in Siberia using field measurements and satellite Interferometric Synthetic Aperture Radar (InSAR), finding transient and spatially heterogenous ground deformation in the permafrost terrain that they attributed to fire effects on the active-layer depth. They concluded that the permafrost depth before the fire plays a crucial role in controlling postfire subsidence and thermokarst evolution.…”
Section: Recent Past and Future Evolution Of Fire Patternsmentioning
confidence: 99%